Disrupsi Digital dan Transformasi Kolektivitas Pedesaan: Media Sosial, Identitas Kaum Muda, dan Pergeseran Komunal di Angar, Maluku - Walima, Nurjani; Rosdawiyah, Rosdawiyah (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
This article analyzes how digital disruption through social media reshapes forms of social collectivity in Angar Village, Maluku, highlighting the central role of rural youth in this transformation. Employing a qualitative approach, the study uses digital ethnography and participant observation, complemented by in-depth interviews with local youth and community figures. Findings reveal that social media not only enables new modes of individual identity expression but also accelerates a shift from traditional, value-based mechanical solidarity to a pattern of networked individualism. This disruption fosters fluid, temporary, and algorithm-driven interactions, yet remains emotionally entangled with local communal ties. Theoretically, the study contributes to the renewal of Durkheimian solidarity theory within the context of digital societies and broadens the scope of rural sociology in Indonesia’s peripheral regions. The novelty of this research lies in its contextualized examination of how youth in digitally connected yet geographically isolated communities negotiate identity and solidarity. It calls for a more adaptive sociological framework to grasp the evolving social dynamics of rural youth in the era of global connectivity, while also encouraging locally grounded digital sociology.